2011
DOI: 10.1016/j.ejcts.2010.10.005
|View full text |Cite
|
Sign up to set email alerts
|

The role of Tc-99m-2-Methoxy-Isobutyl-Isonitrile Single Photon Emission Computed Tomography in visualizing anterior mediastinal tumor and differentiating histologic type of thymoma

Abstract: (99m)Tc-MIBI-SPECT seems to be useful in the evaluation of malignancy in anterior mediastinal mass, and is significantly correlated with the WHO classification and the Masaoka stage. Thus, this technique may add further information to morphological studies for decision making.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 19 publications
0
13
0
Order By: Relevance
“…Malignant cells have a rich metabolism and abundant mitochondria, so they have higher negative trans-membrane potentials. Therefore, it may be possible to use this imaging technique for differential diagnosis of benign and malignant tumors (8,17). The results of the present study revealed that the majority of thymic benign lesions demonstrated no apparent MIBI uptake, while the thymoma groups demonstrated various degrees of increased or concentrated MIBI uptake in the mass regions, with the diagnostic sensitivity set as 95.24%, and the specificity as 90.91%.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…Malignant cells have a rich metabolism and abundant mitochondria, so they have higher negative trans-membrane potentials. Therefore, it may be possible to use this imaging technique for differential diagnosis of benign and malignant tumors (8,17). The results of the present study revealed that the majority of thymic benign lesions demonstrated no apparent MIBI uptake, while the thymoma groups demonstrated various degrees of increased or concentrated MIBI uptake in the mass regions, with the diagnostic sensitivity set as 95.24%, and the specificity as 90.91%.…”
Section: Discussionmentioning
confidence: 58%
“…Certain previous studies have confirmed that the uptake of 99m Tc-MIBI is not only associated with the blood supply, capillary permeability and density of tumor cells, but also with the vitality of mitochondria (13,14,17). Patients with rapid tumor proliferation, high metabolism and low tissue differentiation normally exhibited high uptake of 99m Tc-MIBI in the early phase (18,19).…”
Section: Discussionmentioning
confidence: 81%
“…The combination of repeated CT scan and testing of titin and RyR antibodies could be the bases of non-invasive screening of thymoma. 99m Tc-MIBI single photon emission computed tomography (SPECT) have been used for assessing anterior mediastinal mass and distinguishing the grade of malignancy of thymic epithelial tumors (18). In a preliminary study, we compared the 99m Tc-MIBI image and pathology of thymus in 38 MG patients, and found prominent uptake of MIBI in thymoma, while weak uptake in thymus hyperplasia (unpublished data).…”
Section: Relative Precision In the Main Domains Of Myasthenia Gravis mentioning
confidence: 99%
“…It cannot differentiate between MPM and metastatic pleural malignancy and there is no correlation between SUV value and histological sub-type. In addition, MPM in early stage or MPM with a low proliferation rate could have a low FDG uptake (false negative results) while inflammatory disorders such as rheumatoid pleuritic, tuberculous pleurisy and prior pleurodesis could be FDG-avid (false positive results) (1,(24)(25)(26)(27). To overcome these limits, three-dimensional measurements incorporating total tumor volume and metabolic activity may potentially be more sensitive than the SUVmax not only for diagnosis but also for evaluating the response to treatment (28).…”
Section: Pet-ct Scanmentioning
confidence: 99%